Analisis Faktor – Faktor yang Mempengaruhi Konsumen Untuk Menginap di Hotel Puri Saron - Caesari, Septia; Nugraha, Hari Susanta; Prabawani, Bulan (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
Hotel is a type of industries that produce and provide something in the form of goods and services. Puri Saron Hotel is located in the tourist area of West Lombok over the last five years there is always a rise in the occupancy rate, but the occupancy rate is not optimal because they are under averge. The purpose of this study was to determine the factors that influence consumers to stay at the Hotel Puri Saron. This type of research is exploratory research. Methods of data collection using questionnaires, a preliminary interview and literature study. The sampling technique using sampling techniques and incidental nonprobability sampling.From the analysis of the data found that the factors that influence consumers stay at Hotel Puri Saron consists of price, facilities, location, and quality of service. Factor of price variables consist of suitability given price and the price that has been compared to other hotels. Factor of the facility variable factor is divided into two main facilities and ancillary facilities. Variable locations in the analysis of this study is the flexibility of the consumer to measure the distance of a place to stay with the activities to be carried out. Factor of the variable quality of service consists of the ability of employees in providing services, the capability of communicating with customers, responding to consumer complaints and friendliness of the employees in serving customers. factors based on findings in studies such as the need for evaluation of pricing strategy, the facility is not feasible, as well as improving the quality of service so that consumers are more interested to stay at the Hotel Puri Saron